2018
DOI: 10.1186/s12978-018-0455-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of counsellors and youth-serving professionals about sexual and reproductive health services for adolescents in Soweto, South Africa

Abstract: BackgroundAdolescents in South Africa remain vulnerable to HIV. Therefore, it is crucial to provide accessible adolescent-friendly HIV prevention interventions that are sensitive to their needs. This study aimed to investigate the perceptions of HIV counsellors and other youth-serving professionals about the barriers to providing adolescent youth-friendly sexual and reproductive health services to adolescents in Soweto, South Africa. The study also explored how sexual and reproductive health services in South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…In combination with biochemical prevention methods, such as pre-exposure prophylaxis (PrEP), access to ART programs can significantly curb the HIV epidemic. Attaining this ambitious goal requires innovation that links young South Africans to SRHS, including diagnosis, prevention, treatment, adherence and viral suppression [1, 26–29]. With this in mind, youth-friendly services have been recommended for AYA [6, 30–32].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with biochemical prevention methods, such as pre-exposure prophylaxis (PrEP), access to ART programs can significantly curb the HIV epidemic. Attaining this ambitious goal requires innovation that links young South Africans to SRHS, including diagnosis, prevention, treatment, adherence and viral suppression [1, 26–29]. With this in mind, youth-friendly services have been recommended for AYA [6, 30–32].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in South Africa revealed the barriers of access to reproductive health as lack of confidentiality and privacy, waiting time duration, unpleasant work hours, distance from clinics, and parents' fear when they came to the clinic [18]. Secor-Turner MA & et al reported social stigma, fear of non-confidentiality of services, and the prohibition of their parents and tutors, teenagers as the main barriers of adolescents' access to barriers [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another study in South Africa revealed the barriers of access to reproductive health as lack of confidentiality and privacy, waiting time duration, unpleasant work hours, distance from clinics, and parents' fear when they came to the clinic (14). Secor-Turner MA & et al reported social stigma, fear of non-confidentiality of services, and the prohibition of their parents and tutors, teenagers as the main barriers of adolescents' access to barriers (15).…”
Section: Discussionmentioning
confidence: 99%